The Utilization of Red Mud as a Plant Growing Medium with The Addition of Ultisol Soil Material and Compost - Septi Nurul Aini; Iskandar Iskandar; Darmawan Darmawan (Faculty of Agriculture, Universitas Sebelas Maret, 2017)
The utilization of red mud, which is a residue from the extraction of aluminum from mined bauxite ore, as a plant growing medium, needs to be studied further. There are some chemical aspects that may hinder the growth of, or even cause mortality in, plants such as very high pH, electrical conductivity (EC) and exchangeable Na (Naexch), and very low nutrient elements content. The objective of this study was to investigate the effects of adding Ultisol soil material, mixed with compost, both soil ameliorating agents, to red mud for use as a growing medium for Sengon (Paraserianthes falcataria) seedlings. This study was conducted in two stages, namely: washing of the red mud, and trial planting in the greenhouse using different combinations of the soil ameliorants. Washing of the red mud with tap water was intended to reduce the levels of Na, EC, and pH. Trial planting in the greenhouse was carried out in 2-factorial Completely Randomized Design (CRD). Factor 1 was the proportion of the mixture of Ultisol soil material (sm-Ultisol) and red mud, viz: (1) 1500 g red mud + 0 g sm-Ultisol, (2) 1000 g red mud + 500 g sm-Ultisol, and (3) 750 g red mud + 750 g sm-Ultisol. Factor 2 was the dosage of compost that was mixed with the red mud and sm-Ultisol, namely: 0, 58.6, and 117.2 g/polybag which corresponded to 0, 2.5 and 5 kg/planting hole, respectively. The results of the trial indicated that washing the red mud could reduce the level of EC from 28.70 dS m-1 to 2.68 dS m-1; but it reduced pH and Naexch only from 11.91 and 149.38 cmol(+)kg-1 to become 10.55, and 66.74 cmol(+) kg-1, respectively. A better outcome was obtained after the red mud was washed and then, mixed with sm-Ultisol up to 1:1 proportion in which resulted in lower rates of pH, EC, and Naexch from 10.28, 2.53 dS m-1 and 62.79 cmol(+) kg-1 to 8.65, 2.07 dS m-1 and 45.01 cmol(+) kg-1, respectively. The treatment of using a mixture of 750 g red mud + 750 g sm-Ultisol, and adding compost at 117.18 g/polybag gave the best result in improving the chemical property of the red mud growing medium, and producing the best plant growth among all treatment combinations.